Osteoarthritis Treatment: An In-depth Review of Conventional and Nonconventional Interventions for Symptomatic Relief and Novel Disease Modifying Modalities - Rehman, Mubashar; Madni, Asadullah; Khalil, Saima; Umair, Muhammad; Nasir, Tauseef; Saeed, Omer; Iqbal, Muhammad Naeem (PSM Biological Research, 2017)
Osteoarthritis (OA) is characterized by degradation of joint cartilage which produces severe pain and swelling leading to immobility of the joint. OA can affect people of all age, gender and geographical locations, and the cost associated with long term medication, hospitalization and the loss of daily work hours stigmatizes the patient’s life. Conventionally, the treatment of OA is done with analgesic to relieve pain, but due to notorious side effects profile of NSAIDs and corticosteroids, dependence phenomenon with opioids and continuous underlying degradation of joint, the analgesics cannot be relied upon as sole therapeutic agent. Physical therapies, exercise, modification of lifestyle and use of supportive devices have shown effectiveness in prevention and treatment of mild OA. With the application of multidisciplinary approaches in medical research, many pharmacological and non-pharmacological interventions have evolved with optimistic claims of relieving joint pain and swelling. More recently, disease modifying OA drugs (DMOADs) have shown promising results in preventing cartilage degradation and induction of cartilage regeneration in experimental models as well as initial phases of clinical trials. The diversity of individual needs and complex comorbidities calls for patient oriented treatment plan, a goal which can be achieved effectively by multidisciplinary health care team. This review will provide an in-depth review of all clinically accepted conventional and nonconventional interventions for symptomatic relief of pain as well as novel disease modifying pharmacological and non-pharmacological modalities.